Aspects of the ecology of Leporinus striatus Kner 1858 as a support for its conservation in a Federal Conservation Unit - Talita Rolim de Freitas Lima; Welber Senteio Smith (Acta Scientiarum. Biological Sciences, 2024)
This work describes aspects of the ecology and feeding of Leporinus striatus to fill the gap in information about the species in Brazilian rivers. The study area is in the Ipanema National Forest, Iperó/São Paulo, with the Ipanema River as the place where the specimens were collected in its middle and lower reaches. The size ranged from class 9.0 - 9.5 cm to class 11.5 - 12.0 cm, with females being found in all classes. Class 10 - 10.5 was the one with the highest relative frequency, with males being most abundant in the 9.5-10.0 cm length class and females in the 10-10.5 cm length class. The species' diet was composed of autochthonous species, with the most frequent items being insect fragments and plant material. Based on this information, the species was classified as omnivorous. Underwater observations made it possible to verify that the species is gregarious, inhabiting the water column between midwater and the bottom, preferring stretches with currents and rocky substrate. It performs foraging by leaning its body close to the substrate and biting food on solid surfaces. Small groups made up of at least six individuals shared the areas between rocks and branches. We conclude that, to guarantee the preservation of the species, it is crucial to recognize the significant role played by Conservation Units. However, given the aquatic nature of the species studied, its life cycle is intrinsically linked to stretches that extend beyond the limits of the UC. Additionally, the ecological analyses presented in this study reveal that the species relies on the preservation of a healthy river environment that transcends the boundaries of the conversational unit.